PENGARUH KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN DALAM PENGGUNAAN E-COMMERCE TRAVELOKA (Kasus Di Kelurahan Baranangsiang Bogor Timur) - Fahmi Indra Wajdi; Layung Paramesti Martha; Intan Tri Kusumaningtias (UNIVERSITAS PAKUAN, 2020)
The aims of this study are determine the level of awareness of the Kelurahaan Baranangsiang community brand and to find out how the level of brand awareness influences the community purchasing decisions of Baranangsing Village towards Traveloka E-commerce. The method used in this study was descriptive quantitative using survey research. This research was conducted in Kelurahaan Baranangsiang, East Bogor District, Bogor City with a total of 100 respondents. The sampling technique used in this study is a non probability sampling technique with a purposive sampling method. Quantitative data is presented in the form of a frequency table. Statistical tests were carried out with the help of the SPSS version 25.0 program. Based on the results of the study, it was found that the level of brand awareness of the Baranangsiang Kelurahan community was dominated by people with brand awareness at the brand recognition level. It can be concluded that brand awareness has an influence but the influence given is not too significant. But at the peak level of mind towards the level of awareness of the Traveloka brand weakening, which shows that the peak of one's mind can change along with the development of E-commerce that exists today. Keywords: E-Commerce, Traveloka, Brand Awareness Level, Purchasing Decision.